High modal density active vibration attenuation of bladed structure with a decentralized optimal negative derivative feedback controller. Issue 11 (13th August 2022) - Jamshidi, Rasa; Paknejad, Ahmad; Collette, Christophe
Summary: In this study, an active vibration mitigation of bladed structures with piezoelectric patches utilizing decentralized negative derivative feedback (NDF) controllers is evaluated numerically and experimentally. Such structures have protruding identical blades, which create numerous modes in a short interval of frequency named as high modal density or mode family. Therefore, mitigating these modes is quite challenging. As a case study, a bladed rail is considered with 5 blades, which subsequently has 5 modes in a family of mode in a very short frequency range. A numerical model of the bladed rail including 5 pairs of piezoelectric patches (sensors and actuators) is extracted. Afterwards, a decentralized NDF controller is designed based on maximum damping and H 2 method for this model, which is desirable for reducing vibration corresponding to the first family mode. The numerical results show a perfect performance of the proposed controller on high modal density vibration attenuations. For validating these results, two separate bladed rails have been manufactured, and different piezoelectric patches have been attached to them. The same procedure for designing NDF controller has been done for both of the structures. Experimental results show that the family mode of the bladed rail is completely damped using decentralized NDF controller. Even though the pole‐zero patterns change from the first structure to the second one, the controller can easily mitigate the family mode vibration flawlessly. This shows high applicability of proposed controller on mitigating high modal density modes.